PELATIHAN PEMBUATAN SEDIAAN SERBUK DI MASA PANDEMI DI LINGKUNGAN RT 07 RW 05 KELURAHAN ARJOSARI BLIMBING MALANG - Minah, Faidliyah Nilna; Setyawati, Harimbi; Handaratri, Anitarakhmi; Muyassaroh, Muyassaroh (Dharma: Jurnal Pengabdian Masyarakat, 2022)
The Covid-19 pandemic has hit the world since January 2020, and until now the cases are still increasing. The impact is very global covering various aspects, covering all regions in the world including Indonesia and the city of Malang in particular. As a tourism city that is very superior, of course it is very hard to hit and reduce regional income. As a tourism city that has almost a thousand MSMEs (recorded in the Malang Cooperative Service) that supports the income of the city of Malang, it finally has to go out of business. The group of residents of RT 07 Rw 05, 25% of the population has affected MSMEs. There are those who reduce their business operations, reduce production, reduce employees and some even close their businesses. The lack of income coupled with the low productivity of the citizens adds to the various problems that arise during this pandemic. Coupled with the high prices of basic commodities, agricultural products such as vegetables, fruits, spices, therefore, training activities are needed that can boost the productivity and economy of the residents. This training activity for making powder preparations is expected to add insight to the residents, so that residents can meet their instant food needs independently and if possible they can commercialize the products they produce.